Teori Kontekstual Sebagai Pendekatan Pembelajaran Bahasa Arab yang Menarik - Atika Nur Ardila Hasibuan; Nadya Kartika; Rozi Sakhbana Hasibuan; Sikni Sari Siagian (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Contextual learning theory emphasizes the importance of the learning environment and real-life situations in the learning process. When applied to the teaching of the Arabic language, this approach focuses on integrating language learning with the cultural, social, and historical contexts of the Arab world. By doing so, it aims to make the learning experience more engaging, meaningful, and relevant to the students. This approach recognizes that language is deeply connected to culture, and therefore, language learning should not be isolated from its cultural context. It advocates for the use of authentic materials, such as literature, music, and films, to provide learners with a holistic understanding of the language and its cultural significance. Furthermore contextual learning theory encourages interactive and communicative language activities that mirror real-life language use, enabling students to develop practical language skills that are applicable to genuine social and cultural settings. In the context of teaching Arabic, this approach can enhance students' motivation and interest in learning the language by making the learning experience more dynamic and immersive. It also supports the development of students' intercultural competence by fostering an understanding of the cultural nuances embedded in the language. In summary, the contextual learning theory as an approach to teaching Arabic language offers a comprehensive and engaging framework that integrates language learning with thecultural, social, and historical contexts of the Arab world. By doing so, it aims to make the learning experience more meaningful, relevant, and captivating for students.